The Method Study And Stability Testing on Liquid Probiotic Products at CV. Pradipta Paramita, Karanganyar Regency, Central Java - Alzahni Meila Putri; Ren Fitriadi; Agnes Heratri; Maghfira Selia Irawati; Kamilatun Nisa' Agustina (Journal Of Artha Biological Engineering, 2026)
Evapond Bacillus is a liquid probiotic product developed to enhance the health of fish and shrimp. Maintaining its quality can be achieved through encapsulation using coating materials. This study applied an experimental method with three treatments and one replication. The encapsulation material concentration was set at 10% of the liquid volume, with variations in the ratio of maltodextrin and guar gum, namely (70%:30%), (50%:50%), and (60%:40%), each prepared in 100 ml of water. The experiment was conducted for two months to evaluate product stability after encapsulation. The results showed that the combination of maltodextrin and guar gum did not significantly affect the stability of Evapond Bacillus. However, the (60%:40%) ratio demonstrated relatively better performance compared to other treatments. These findings indicate that although the differences were not statistically significant, certain compositions may provide more favorable outcomes. Further studies are recommended using additional or alternative encapsulation materials to obtain more optimal and applicable results.